INVENTARISASI SPESIES FAMILI ARACEAE TAMAN BIODIVERSITAS HUTAN HUJAN TROPIS LEMBAH BUKIT MANJAI - Febrian, Muhammad Rifqy; Rezeki, Amalia; Widiyastuti, Dewi Amelia (Biospecies, 2026)
Biodiversity Park of Bukit Manjai Valley, South Kalimantan. The research employed a cruising method through direct observation and morphological documentation. Seven Araceae species were identified: Alocasia princeps, Alocasia sarawakensis, Amorphophallus borneensis, Amorphophallus paeoniifolius, Amorphophallus muelleri, Amydrium medium, and Schismatoglottis ahmadii. Each species showed distinct morphological traits and ecological adaptations to the tropical rainforest environment. Measurements of abiotic factors like temperature, humidity, light intensity, soil pH, and wind speed indicated suitable habitat conditions for Araceae. Scientifically, the study contributes valuable data to the enrichment of local taxonomic databases, serving as a reference for botanical classification and species verification in South Kalimantan. Moreover, the documentation strengthens baseline information needed for the conservation planning of endemic and potentially threatened Araceae species in the region. The results also have applied value for the development of local-content-based learning media in higher education, particularly in the Phanerogamae course.